A Conceptual Framework for 3D Hologram Talking-Head Character Design - Ahmad Zamzuri Bin Mohamad Ali (Tanjung Malim, 2023)
A Conceptual Framework for 3D Hologram Talking-Head Character Design by Ahmad Zamzuri Bin Mohamad Ali